Design of an intelligent disinfection control system based on an STM32 single-chip microprocessor by using the YOLO algorithm - Xueyi Wang; Xianrong Li; Haiying Du; Jing Wang (Scientific Reports)
Abstract The novel coronavirus (COVID-19) has affected more than two million people of the world, and far social distancing and segregated lifestyle have to be adopted as a common solution in recent years. To solve the problem of sanitation control and epidemic prevention in public places, in this paper, an intelligent disinfection control system based on the STM32 single-chip microprocessor was designed to realize intelligent closed-loop disinfection in local public places such as public toilets. The proposed system comprises seven modules: image acquisition, spraying control, disinfectant liquid level control, access control, voice broadcast, system display, and data storage. The STM32 microcontroller is the main control chip and collects the disinfectant liquid level information and crowd density by using flow sensors, pressure and image. Single chip microcomputer enabling composite control of disinfectant concentration and liquid level through proportion integration differentiation (PID) control and logical increase/decrease ratio control. The use of the You Only Look Once (YOLO) algorithm aids in improving the accuracy of human target recognition, dynamically obtaining the crowd density, and regulating the spraying strategy. A comparison of the dynamic changes in crowd density with the user-defined crowd density threshold is performed to optimize the access control time and model parameters and obtain the optimal access control time limit. This approach enables dynamic optimization and intelligent control of the proposed full-cycle, closed-loop disinfection model for public toilets, effectively reducing the risk of virus transmission.